PANDANGAN PEMANGKU KEPENTINGAN TERHADAP USAHATANI BERKELANJUTAN SAYURAN DATARAN TINGGI DI DESA SINISIR KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (The View of Stakeholders on Sustainable Highland Vegetable Agribusiness in Sinisir Village, Modoinding Sub District, South Minahasa Regency) - Mamahit, Charles Christover; Waney, Nordy L. F.; Mandei, Juliana R. (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to to describe the views of stakeholders on sustainable upland vegetable farming in Sinisir Village, Modoinding District. Stakeholders studied consisted of farmers, traders and household consumers. Highland vegetables consist of carrots, cabbage, chinese cabbage, etc. This study uses a survey method, data collection using purposive sampling method by determining the specific characteristics of respondents in accordance with the research objectives. The number of samples is 50 respondents. The data used in the study are primary data, 2020. The data analysis was descriptive using a Likert scale. The research results showed that most of the farmers agreed with the application of the principles of sustainable highland vegetable farming. The obstacle faced by farmers is the lack of availability of organic fertilizers and pesticides when they are needed by farmers and in the quantities needed by plants. Most of the traders agree with the application of the principles of sustainable upland vegetable farming. Trade intermediaries need guarantees that vegetable products are produced by applying sustainable principles to upland vegetable farming. Most consumers agree with the implementation of sustainable farming. The problem at the consumer level is the guarantee that the vegetable products purchased are the result of farming that applies the principles of sustainable highland vegetable farming. There is a need for a framework developed jointly by stakeholders that ensures the application of sustainable principles in upland vegetable farming, includingÂ